The Impact of the strategy of Guided Imagination in academic achievement of Second Grade Female Students in Chemistry and Visual Intelligence - Al Amiry, Zainab Aziz; Hatem Al-Kurji, Khaled Hussein (Opción, 2019)
The study aimed to know the effect of using the guided imagery strategy in the achievement of second grade students in chemistry and visual intelligence, and the sample of the study consisted of (44) students from the second grade average students were distributed to two experimental groups (22) and a con- trol group (22). Reward the two groups in the variables: (the average achieve- ment of the first course grades, chronological age in months, intelligence test, previous information). To achieve the objective of the study, an educational material was adopted according to the strategy of guided imagery and visual intelligence testing. After calculating psychometric properties, the data were treated statistically using SPSS statistical program. The results showed that there is a statistically significant difference between the students of the ex- perimental group who studied according to the guided imagination strategy and the students of the control group who studied according to the traditional method of achievement and visual intelligence for the experimental group. Accordingly, the researchers recommend the adoption of a strategy of guided imagery in the teaching of chemistry, and propose to conduct further studies of different stages and subjects to learn their impact on science fiction and visual intelligence.